Lilin Aromaterapi Dari Minyak Jelantah : Solusi Alami Menghilangkan Bau Kandang Ternak Di Desa Pecekelan - Handoyo Handoyo; Mohammad Syafiq Mujtaba; Khamdan Nahi Asrofi; Sugeng Riyadi; Yanafi Rahman; Valentiana Afifah; Adam Zidan Taufiqurohman; Ratna Wahidatunnisa; Syarifatun Nisa; Vivi Alfinia; Nur Maziyah; Rahayu Dewi Kholifah; Ulul Azmi Hasanati (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
The people of Pecekelan Village, Sepuran District, Wonosobo Regency, Central Java, face a unique challenge in the form of an unpleasant odor from cattle pens adjacent to settlements, reflecting a strong agrarian life but interfering with daily comfort. In response to this situation, the Community Service Lecture (KPM) team from the University of Al-Quran Science developed an innovation in making aromatherapy candles made from used cooking oil as a natural solution to eliminate the smell of cages. This initiative not only aims to overcome the odor problem, but also to utilize household waste into useful products, create economical and environmentally friendly solutions, and improve the quality of life of village communities. This program is carried out through a series of activities including socialization, aromatherapy candle making training, product trials, and basic entrepreneurship training. Early results show effectiveness in reducing cage odors, improving home comfort, and creating a healthier environment. Furthermore, this program increases public awareness about waste management, encourages active participation in maintaining environmental cleanliness, and opens up new economic opportunities. This simple but impactful innovation has the potential to be applied in other areas with similar problems, promoting a sustainable approach in addressing environmental challenges at the household level while empowering local communities.